How Does Chinese Outward Foreign Direct Investment Respond to Host Country Cultural Tolerance and Trust? - Liu, Haiyue; Wang, Yuhan; Zhang, Qin; Jiang, Jie (Frontiers in Psychology, 2022)
Based on 2010 to 2019 Chinese outward foreign direct investment (OFDI) panel data from 39 host countries, this paper studies the relationships between host country cultural characteristics and Chinese OFDI. The OLS regression results show that the cultural tolerance and trust in the host countries are significantly positively correlated with Chinese OFDI, which are robust according to the system GMM tests. Further analysis reveals that cultural tolerance is more positively related to Chinese OFDI in host countries with higher legislation and economic freedom, while cultural trust is positively associated with Chinese OFDI in host countries with lower legislation and economic freedom. In addition, higher cultural tolerance and trust promote Chinese OFDI in countries with greater cultural distance. Unlike traditional studies based on cultural distance in international trade, using more representative cultural characteristics, this paper provides references to Chinese OFDI decision-making based on the root characteristics associated with heterogeneous cultural influences.